2003
DOI: 10.2460/ajvr.2003.64.1414
|View full text |Cite
|
Sign up to set email alerts
|

Use of the impulse oscillometry system for testing pulmonary function during methacholine bronchoprovocation in horses

Abstract: In contrast to CRT parameters, IOS parameters were significantly more sensitive for testing pulmonary function. The IOS provides a practical and noninvasive pulmonary function test that may be useful in assessing subclinical changes in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…Histamine challenge score also produced the highest proportion of correctly classified horses (coughing and nasal discharge groups) in discriminant analysis. Histamine bronchoprovocation revealed significant differences between healthy control horses and the group of RAO‐affected horses with neither owner‐reported coughing nor nasal discharge, and also demonstrated the most consistent differences between the healthy control horses and all the RAO‐affected groups, confirming observations from experimental studies which have shown that RAO‐affected horses kept in a low‐dust indoor environment will continue to show airway hyperresponsiveness , in contrast to those kept permanently on pasture ). Several studies on human asthma have shown that airway hyperresponsiveness persists in many individuals who consider themselves to be in remission of asthma .…”
Section: Discussionsupporting
confidence: 76%
“…Histamine challenge score also produced the highest proportion of correctly classified horses (coughing and nasal discharge groups) in discriminant analysis. Histamine bronchoprovocation revealed significant differences between healthy control horses and the group of RAO‐affected horses with neither owner‐reported coughing nor nasal discharge, and also demonstrated the most consistent differences between the healthy control horses and all the RAO‐affected groups, confirming observations from experimental studies which have shown that RAO‐affected horses kept in a low‐dust indoor environment will continue to show airway hyperresponsiveness , in contrast to those kept permanently on pasture ). Several studies on human asthma have shown that airway hyperresponsiveness persists in many individuals who consider themselves to be in remission of asthma .…”
Section: Discussionsupporting
confidence: 76%
“…As previously reported, the horses studied during phase 1 underwent IOS testing before and after sedation . The R 5 : R 10 ratio has been validated previously as an indicator of airway obstruction in horses with heaves . The resonant frequency indicates the frequency at which the inflation pressure and elastic recoil cancel out, resulting in a reactance equal to zero.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, alternative more sensitive methods have been evaluated in recent years. These include impulse oscillometry, which measures respiratory resistance and reactance at various frequencies , tidal breathing flow‐volume loops , volumetric capnography and forced expiratory flow‐volume curve analysis , with the most discriminatory and commonly employed method at present being impulse oscillometry.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%